Contribution to the Cantatas on the Anniversary of the Galley Slaves’ Liberation - Berkesi, Sándor (Acta Neerlandica, 2026)
New Hungarian choral works were born on another jubilee, i.e., on the 300th anniversary of the Protestant galley slaves’ liberation. They are the ‘little sisters’ of the oratorio Budavári Te Deum, these cantatas are in the order of their completion: Sándor Szokolay: Cantata to the Memory of the Galley Slaves, Lajos Vass: Furor Bestiae, Zoltán Gárdonyi: Memento. Composers use the text written by Ferenc Otrokocsi Fóris and other galley slaves who records the story of his deportation, sufferings and liberation. The last two pieces of music were composed in October 1975 and dedicated to the choir ‘Kántus’ of the Reformed College of Debrecen. Their world premiere took place on 11 February 1976 in the Reformed Great Church in Debrecen, in the framework of festivities dedicated to the anniversary of the liberation of the galley slaves, the conductor was the writer of this article.